Audit of Revenues and Expenditures in Budget Organizations - To‘xtasin Abdiqodirovich Qo‘shayev (International Journal on Economics, Finance and Sustainable Development, 2021)
This article describes the procedure for valuing financial assets at amortized cost and fair value in accordance with International Financial Reporting Standards, and defines the concepts of amortized cost and fair value of financial assets. The issues of business model in the selection of valuation approaches for financial assets are covered. In addition, practical procedures are used to assess the fair value of financial assets through other comprehensive income and profit and loss statements, and to determine the initial value of financial assets.